Memorials, Shrines and Umbrellas in the Rain: Poetry and 11-M - Jill Robbins (Studies in 20th & 21st Century Literature, 2012)
This project examines the representations in recent Spanish poetry of violence, solidarity, and memory, as these intersect with ethnic, linguistic and religious otherness, globalization, communication technology, and nationalisms. The lens through which the analysis is refracted is the poetic response to the Islamist terrorist bombings of working-class commuter trains in Madrid on March 11, 2004 (known in Spain as 11-M). This event, which occurred days before national elections, exposed the contradictory cultural forces that underlie notions of the national identity, economic transformation, the role of the media, and the social contract in Spain today. This became apparent in the massive demonstrations against neoliberalism, Spain’s alliance with the US in the “war on terror,” and Basque terrorism on 12-M. These popular protests were soon followed by police investigations, legal battles, and, finally, cultural memorials. Still, the battle to give meaning to these events continues to rage in politic circles, in cultural artifacts, and in the press.
Keywords: Spanish poetry; violence; solidarity; memory; otherness; religion; ethnic; linguistic; Islamic terrorist; bombings; Madrid; national identity; social construct